The Influence of Problem Based Learning and Media to Increase Student Interest and Learning Outcomes - Siti Muliana Tambunan; Jamalum Purba; Freddy Tua Musa Panggabean (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The aim of this research is to find out whether there is an influence of the use of problem and video based learning models on student interest and learning outcomes. This research was conducted at SMA Negeri 14 Medan and the research population was all class. In the research, the pretest score was 34.85 and the posttest score was 80.28. Normality and homogeneity tests were carried out and the results showed normal distribution. In hypothesis testing using One Sample T-Test, a Sig.(2-Tailed) value of 0.002 was obtained. Therefore, a value of 0.002< α (0.05) means that the hypothesis is accepted, which shows that there is an influence of the use of problem-based learning models and videos on student learning outcomes in chemical bonding material. Meanwhile, for the results of student interest in learning, the average score obtained was 76.06 in the high category. This shows that there is an influence of the use of problem-based learning models and videos on students' learning interest in chemical bonding material.